Rheological Properties of Bread Dough Formulated with Wheat Flour–Organic Calcium Salts–FOS-Enriched Inulin Systems - Salinas, María Victoria (2014)
The objective of this work was to study the effect of organic calcium salts–fructooligosaccharide (FOS)-enriched inulin systems on dough structure and rheological properties of wheat flour dough. Wheat flour was enriched with calcium lactate (CaLa₂) or calcium citrate (Ca₃Ci₂) (from 1,080 to 2,520 ppm Ca) and FOS-enriched inulin (In) (from 0 to 13 %, w/w flour basis). Alveographic, texture, relaxation, and viscoelasticity properties of dough were analyzed. Wet and dry gluten quantity, related to scanning electron microscopy structure, was also determined. Tenacity, extensibility, and deformation energy of dough decreased with the increment of In content. When CaLa₂ was employed, they changed mainly with fiber, hiding the effect of lactate; whereas with Ca₃Ci₂, these parameters were not only affected by the fiber, but also by the salt. At In 6.5 %, high calcium content (2,520 ppm Ca) produces an increase in hardness and a decrease in cohesiveness for citrate ion; the opposite effect was detected with lactate ion. These parameters decreased at high content of In (13 %). Adhesiveness was dependent only on In level; more adhesive dough at In > 6.5 % were obtained, mainly in the case of CaLa₂. Ca₃Ci₂ prevents the decrease in adhesiveness at In > 12 %. At high calcium levels, high In produced more elastic dough only in the presence of citrate; for lactate, the predominant factor was In. Lactate anion destabilizes protein structure, and together with In favors formation of a less elastic gluten network. On the other hand, the stabilizing effect of citrate ion in a firm network was enhanced by FOS-enriched inulin.